Determination of breeding seasonality in rusa deer (Rusa timorensis) stags via serum testosterone profiling - Wan Jaafar, Wan Nor Fitri; Haron, Abd Wahid; Yusoff, Rosnina; Abdullah, Faez Firdaus Jesse; Zainal Abidin, Siti Aimi Sarah; Mohd Lila, Mohd Azmi; Che' Amat, Azlan; Rashid, Muhammad Azrolharith; Omar, Mohamed Ariff (Science Publications, 2017)
Breeding seasonality in mammals is influenced by the environmental changes and the endocrine response of the animals to that changes. Comprehension in breeding seasonality enables better reproductive management consequently maximizing the reproductive potential of the stags. Despite that, the study in breeding seasonality in Rusa deer (Rusa timorensis) is still scarce. Five healthy and matured stags were selected for this experiment. Semen were collected using electroejaculator at a monthly interval from April to September 2012. Semen motility is determined using a percentage. Meteorological data were obtained from the nearest weather station located in Petaling Jaya. Serum was utilized for the radioimmunoassay determination of serum testosterone profile. The warmest condition was in June and it’s coolest in November of 2012. There was a strong, positive correlation between testosterone concentration and general motility (p<0.05) with a correlation coefficient, rs = 0.943. Meteorological data alone; temperature, relative humidity and rainfall are insufficient to determine the breeding seasonality in Rusa deer, bearing no significant correlation with serum testosterone concentration and sperm motility. Rusa deer stags is reproductively active from April to July, low in August and starts to rise again in September. Therefore, this study demonstrates that breeding seasonality in Rusa deer stags can be determined via serum testosterone profiling.